Analysis of the Influence of Experience, Time Budget Pressure, and Risk of Errors on the Quality of External Audit Public Accounting Firm West Jakarta Region - Meilani, Elena Fiska; Nuryatno, Muhammad (Universitas KH. Abdul Chalim Mojokerto, 2024)
This research aims to determine the influence of Audit Experience, Time Budget Pressure, and Risk of Error on the Quality of External Audits of West Jakarta Regional Public Accounting Firms. This research was carried out using quantitative methods. The data used in this research is primary data obtained from questionnaires of auditors in KAP in the West Jakarta region. This research analysis method uses questionnaire data. The research results show that auditor experience, time budget pressure, and risk of error positively affect external audit quality.